A 2 × 2 planar array of Clover‐leaf shaped printed antennas for weather‐monitoring based applications. Issue 4 (31st December 2021) - Kola, Kalyan Sundar; Chatterjee, Anirban; Jagannath, Ravi Prasad K.
Abstract: This article presents a 2 × 2 printed planar array and its single element for weather‐monitoring (8.175–8.125 GHz) related applications. The proposed array's single antenna prototype is a nature‐inspired‐based design and is derived from natural Clover‐leaves . The single proposed element gives an appreciably decent gain and heavily suppresses cross‐polarization (x‐pol.) along its main beam direction. The array is designed using the Wilkinson divider‐based corporate feed network to achieve a low loss level and better bandwidth response. The sole fabricated element resonates at 8.19 GHz and offers 7.85 dBi peak gain and 336 MHz impedance bandwidth, respectively. Similarly, 12.30 dBi gain and 263 MHz impedance bandwidth have been achieved from the array geometry at the resonating frequency of 8.195 GHz. The prototypes' computed correction factor is 40.64 and 36.20 dB/m, respectively. Both the prototypes provide 100% bandwidth coverage for weather‐monitoring applications under X‐band. Both the prototypes provide a below −35 dB x‐pol. Along its main beam direction. They offer reasonably good radiation efficiency of 92.77% and 89.16%, respectively. An excellent agreement has been entrenched in between measured and simulated results of the prototypes.